2016
DOI: 10.1038/srep39355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and safety for recombinant human adenovirus-p53 in the control of the malignant pleural effusions via thoracic perfusion

Abstract: A certain number of studies have showed that p53 gene transfer has an anti-tumor activity in vitro and in vivo. This study was to evaluate the efficacy and safety of thoracic perfusion of recombinant human adenovirus p53 (rAd-p53, Gendicine) for controlling malignant pleural effusion (MPE). We searched for the relevant studies from the database of MEDLINE, Web of Science, EMBASE, Cochrance Library and CNKI to collect the trials concerning the efficacy and safety of rAd-p53 to treat MPE. Fourteen randomised con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Intrapleural injection of anti-tumor chemotherapyagents has been suggested to be used in controlling of MPE because it is believed that when the drug is injected directly into the pleural cavity, its concentration acted on the pleura is much higher than by intravenous injection [ 2 ]. Today, there is no cure for metastatic lung cancer, however, some new molecular targeted drugs have been found to be useful in the treatment of lung cancer [ 3 ]. In several clinical trials, first-line combination chemotherapies containing bevacizumab are revealed to improve clinical outcomes in patients with advanced non-squamous NSCLC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrapleural injection of anti-tumor chemotherapyagents has been suggested to be used in controlling of MPE because it is believed that when the drug is injected directly into the pleural cavity, its concentration acted on the pleura is much higher than by intravenous injection [ 2 ]. Today, there is no cure for metastatic lung cancer, however, some new molecular targeted drugs have been found to be useful in the treatment of lung cancer [ 3 ]. In several clinical trials, first-line combination chemotherapies containing bevacizumab are revealed to improve clinical outcomes in patients with advanced non-squamous NSCLC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, most patients with lung cancer often develop MPE during the course of the disease, which results in a significant decline in the quality of life (QOL) of the patient and leads to a reduction in the expected survival of the patient [ 2 ]. Currently, drainage of pleural effusion, thoracic perfusion of chemotherapeutic drugs, and systemic chemotherapy are the primary means of handling MPE [ 3 ]. Although MPE is very common, the current understanding of MPE is still limited and there are controversies in almost every aspect of diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Numerous drugs including paclitaxel, bevacizumab and cisplatin have been administered into the pleural space in clinical trial settings to control malignant pleural effusion, alleviate symptoms, or slow disease progression. 12,[15][16][17][18][19][20][21][22][23][24][25] To the best of our knowledge, the direct administration of curcumin into the pleural cavity has never been reported. The purpose of this study was to evaluate the safety and bio-distribution of a pharmaceuticalgrade liposomal curcumin formulation after intrapleural administration in healthy rats.…”
Section: Introductionmentioning
confidence: 99%
“…The present treatments of MPE include the drainage of pleural effusion, intrapleural chemotherapy and systemic chemotherapy. Unfortunately, not all patients with MPE can benefit from quasi chemotherapy and treatment [ 3 ]. During the last decade there has been significant progress in unravelling the pathophysiology of MPE, as well as its diagnostics, imaging, and management [ 4 ].…”
Section: Introductionmentioning
confidence: 99%